Ефективне управління документообігом як один з важливих елементів ведення бізнесу - Ярка, Уляна (Видавництво Львівської політехніки, 2015)
Document workflow management is a critical element of business. The concept of documentation depends on the type of business and type of documentation. Good management leads to increased competitiveness.
Keywords: інформація; документообіг; управління; бізнес-процеси; підприємство; автоматизація